Synthesis and characterization of zinc-layered 2, 4, 5 trichlorophenoxybutyric acid under aqueous condition / Nur Hani Ab Rahman - Ab Rahman, Nur Hani (Faculty of Applied Sciences, 2016)
The synthesis of zinc-layered 2, 4, 5-triclorophenoxybutyric acid (ZTBA) and the characterization of the nanohybrid compound by using powder x-ray diffraction (PXRD), Fourier Transform Infrared (FTIR), Thermogravimetric and Derivative Thermogravimetric Analysis (TGA/DTG) and Elemental Analysis (CHNS) has been developed. The synthesis of the ZTBA nanohybrid compound was successfully prepared by using anion-exchange method. The pure phase and well-ordered zinc-layered 2, 4, 5-trichlorophenoxybutyric acid was synthesized at 0.1 M 2, 4, 5-trichlorophenoxybutyric acid (TBA) and with a basal spacing of 13.0 Å. The FTIR spectra show resemblance of TBA with ZnO absorption characteristics. The percentage loading of guest anions, TBA in the zinc layered hydroxide was calculated to be about 51.92 % .The total weight loss by using TGA / DTG is calculated to be at about 63.5 % in the range of 90 - 1000⁰C.